Geometric calibration of multibeam bathymetric data using an improved sound velocity model and laser tie points for BoMMS. (15th November 2017) - Yang, Fanlin; Bu, Xianhai; Ma, Yue; Lu, Xiushan; Wang, Mingwei; Shi, Bo
Abstract: When the incidence angle is beyond 60°, the geolocation accuracy of multibeam bathymetries is low using the conventional method of sound-ray tracing. A new geometric calibration method is proposed to address the geolocation problem for the multibeam bathymetries at large incidence angles. First, based on the sound velocity profile (SVP) data in survey regions and the surface sound velocity (SSV) data along tracks, an improved sound velocity model (SVM) is established for the initial sound-ray tracing using the algorithms of empirical orthogonal function (EOF) analysis and the weighted linear interpolation. Then, groups of tie points are extracted, which are located at the border between water and land, and are acquired by the laser scanner and multibeam echo sounder. The laser tie points, which have better geolocation accuracy, are used to calculate the rotation angle and scale coefficient to calibrate for every sound ray corresponding to an incidence angle beyond 60°. The calibration results showed that the horizontal and elevation accuracies of the multibeam measured points were approximately 2.5 cm (increased by 12.5 cm) and 1.3 cm (increased by 3.6 cm), respectively. This method has a significant effect on improving geolocation accuracy for multibeam bathymetries with large incidence angles. Highlights: An improved sound velocity model for shallow water is proposed for ray tracing. The laser points acted as tie points were extracted to calibrate the bathymetries near the water surface. The anti-collision rubbers or buoys are used to act as feature targets to extract tie points for the calibration.